Life imprisonment in England and Wales and Turkey in the context of Europe: a comparative jurisprudential study - Celiksoy, Ergul (2022)
This thesis is a comparative jurisprudential study of life imprisonment in England and Wales (E&W) and Turkey. It seeks to examine and compare the imposition and implementation of and release from life imprisonment in E&W and Turkey, as the two legal systems with the highest number of life prisoners in Europe. European human rights standards for life imprisonment are used as the yardsticks of comparison. The thesis examines whether human-rights-compliant life imprisonment is plausible under European human rights law, and if so, whether life sentences in E&W and Turkey are used in a human-rights-compliant way. At the European supranational level, life imprisonment is considered an acceptable form of punishment when its imposition and implementation are governed by human rights norms and standards. The comparative findings of the present thesis demonstrate that most forms of life sentences in E&W and Turkey generally satisfy the fundamental requirements of human-rights-compliant life imprisonment. Although there are certain shortcomings when judged against human rights standards, generally the defects in most forms of life sentence in E&W and Turkey do not reach a point to consider them inhuman or degrading. However, there are a few forms of life imprisonment in the two legal systems that cannot be considered human-rights-compliant, and hence, are unacceptable under European human rights standards. These are life sentences with whole life terms in both E&W and Turkey because they do not provide for any realistic prospect for release from life imprisonment. Further, aggravated life sentences of Turkey cannot be considered human-rights-compliant because it has a punitive rather than rehabilitative character. After conducting a comprehensive, critical comparison, the thesis made some recommendations for what should be done in E&W and Turkey in order for life sentences to fully meet the requirements of human-right-compliant life imprisonment.